S35 Coxsackie and adenovirus receptor (CAR) provides protection against allergic airway inflammation. (December 2018) - Ortiz Zapater, E; Ranz-Jimenez, I; Roberts, L; Santis, G; Parsons, M
Abstract : Introduction and objectives: Loss of epithelial integrity in response to allergen exposure can trigger the onset of airway inflammation. Trans-epithelial migration (TEpM) of leukocytes during inflammation requires engagement with receptors expressed on the basolateral surface of the epithelium. One of these receptors is the coxsackie virus and adenovirus receptor CAR, that stabilises epithelial cell-cell adhesions. Our studies have shown that CAR is regulated through phosphorylation by PKCδ to control junction stability (Morton et al, 2013). TNFa phosphorylates CAR, which leads to an increase in the TEpM of primary monocytes and neutrophils. CAR is also hyper-phosphorylated in vivo in induced acute and in chronic lung inflammation models and this response is required to facilitate immune cell recruitment (Morton et al, 2016). The goal of this study is to test our novel hypothesis that CAR is a central co-ordinator of lung inflammation through control of leukocyte recruitment, infiltration and tissue remodelling. Methods: House dust mites (HDM) are one of the most common aeroallergens worldwide and most asthmatics are HDM allergic. We have performed HDM in vitro experiments on human bronchial epithelial cells (16HBE). We have developed a conditional mouse model in which we have depleted CAR specifically in the club cells from the lung bronchial epithelium ( Ccsp-cre CAR flox/flox mice) after Tamoxifen intraperitoneal injection. The effects of allergen exposure by intranasal administration of HDM were then assessed over 5 consecutive weeks. Results: HDM in vitro treatment on 16HBE cells leads to junction instability and to CAR phosphorylation. The release of HDM-dependent inflammatory cytokines is reduced in CAR depleted 16HBE cells. In vivo, specific epithelial deletion of CAR in Club cells significantly reduced peribronchial and perivascular infiltration by inflammatory cells, a quasi-absence of goblet-cells hyperplasia, fewer eosinophils in the lung tissue and decreased concentrations of IL-13 and IL-33. CAR has an effect in the extracellular matrix proteins deposition as the CAR KO mice show higher levels of collagen I and a-SMA deposition independently of the HDM challenge. Conclusions: These data demonstrate that CAR plays a key role in regulating inflammation and subsequent activation of the immune response after HDM challenge, which potentially enables the development of novel therapeutic approaches in the future.